Development of a Novel Umbilical Retraction Mechanism for a Launch Vehicle - Nguyen, Manh-Cuong; Pham, Van-Tung; Nguyen, Van-Tinh; Nguyen, Duy-Hung (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
Umbilical or umbilical cable supplies are required for an apparatus, such as a space vehicle, or for a person, a diver, or an astronaut. For launch vehicles, umbilical cables provide essential elements like electrical power, communication, and pressurized gases before liftoff. Ensuring the retraction of these cables is crucial for preventing potential damage during the launch process. This paper addresses a novel mechanism for umbilical retraction in the launch vehicle loading process. This mechanism is based only on the principles that borrow the vehicle’s launch motion to generate a cable-cutting action, and no power is required. The new design of the umbilical retraction device is optimized through simulation and validated by the experiment. The results confirm that the introduced mechanism works effectively with a maximum number of 20 umbilical cables consisting of two forms, namely PVC and metal covers.